Geographically restricted heterogeneity of the Plasmodium falciparum circumsporozoite protein: relevance for vaccine development. - Doolan, D L (1992)
The design of a subunit vaccine against the malaria parasite relies on the epitopes recognized by T cells being identified and polymorphisms therein being defined. Here we present the analysis of a 354-bp fragment of the circumsporozoite (CS) protein encompassing defined proliferative and cytotoxic T-cell recognition regions. We reveal that the polymorphism of CS protein T-cell sites appears to be very limited among Plasmodium falciparum isolates prevalent in certain geographical regions, in particular Papua New Guinea. Furthermore, the more extensive polymorphism noted in other areas appears to be restricted. Although the extent of variation observed for the T-cell recognition domains suggests that any vaccine designed to stimulate this form of immunity will need to be polyvalent, this variation appears to be finite and the combination of peptides necessary for inclusion in a polyvalent vaccine may be small. If ways to increase immune responsiveness can be found, then a vaccine designed to stimulate CS protein-specific T-cell activity may prevent malaria.